Pengaruh Entrepreneurial Marketing terhadap Kinerja Biro Penyelenggara Perjalanan Ibadah Umrah di Provinsi Sulawesi Selatan - Putri, Mediany Kriseka; Sapriadi, Sapriadi (Universitas Batanghari Jambi, 2024)
The phenomenon of Umrah worship is currently increasing, as evidenced by the large number of pilgrims who perform Umrah every year. The Umrah pilgrimage has also become a business phenomenon for many industries, including the travel and tourism industry. The Umrah pilgrimage travel agency has an important role in facilitating pilgrims in performing the Umrah pilgrimage by meeting their needs such as transportation, accommodation, and so on. Therefore, the increase in the phenomenon of the Umrah pilgrimage also affects the performance of bureaus organizing the Umrah pilgrimage. Based on data from the Ministry of Religion, there has been a significant increase in the number of bureaus organizing Umrah services in the province of South Sulawesi in 2020 by 46 bureaus. Entrepreneurial Marketing is the ability to develop innovative and effective marketing strategies. By using the right marketing strategy, the Umrah travel agency can increase the number of pilgrims registered with the company, while increasing business profits. This can be an opportunity for Umrah travel agents in South Sulawesi Province to improve their performance and develop their business by observing this trend. In this study a correlative descriptive research method was used and 100 questionnaires with a five-point Likert scale were distributed among someone who worked at the Umrah travel agency in South Sulawesi province using the simple random sampling method. To analyze the data, structural equation modeling based on partial least squares was used using SmartPLS. The purpose of this study is to investigate whether Entrepreneurial Marketing has a positive and significant influence on the performance aspects of bureaus organizing Umrah travel in the province of South Sulawesi.